(untitled) (Al-Aasar, 2026)
This research article presents a comparative and analytical study of the concept of God in Judaism, Christianity, and Islam. These three religions are known as the Abrahamic faiths because their teachings are historically linked to the monotheistic message of Prophet Abraham (peace be upon him). All three religions believe in one supreme, all-powerful, and creator God; however, there are both similarities and significant differences in their understanding of the nature of God, His attributes, His oneness, His relationship with human beings, and the method of worship. This study examines these similarities and differences through a scholarly and comparative approach in order to clarify the theological and historical development of the concept of God in these religions.The research is based on primary sources, namely the Torah, the Gospel, and the Qur’an, along with secondary sources including classical commentators, theologians, and modern scholars of comparative religion. In Judaism, the concept of God is centered on strict monotheism, the transcendence of God, and the covenantal relationship between God and the Children of Israel, along with strong emphasis on divine law. In Christianity, the doctrine of Trinity, the belief in Incarnation, and the concept of divine love and salvation are central to the understanding of God. In Islam, the concept of God is based on pure monotheism (Tawhid), the absolute unity and uniqueness of God, the perfection of divine attributes, and the direct relationship between the Creator and His servants without any intermediary in divinity.Using a comparative research method, the article analyzes the concept of God in the three religions from multiple perspectives, including the meaning of divine unity, attributes of God, the relationship between God and humanity, the nature of revelation, the concept of worship, and the doctrine of salvation. The study shows that although Judaism maintains a strong monotheistic belief, its understanding of God is closely connected with historical and communal identity. Christianity presents the unity of God through the doctrine of Trinity, which includes the Father, the Son, and the Holy Spirit. Islam, on the other hand, presents the concept of God as absolutely one, indivisible, and incomparable, rejecting any form of partnership or incarnation.The findings of the study indicate that the fundamental message of all three religions is belief in one God, but historical developments and theological interpretations have led to differences in understanding His nature. Among the three, Islam presents the most systematic, clear, and uncompromising form of monotheism, which is reflected not only in belief but also in worship and daily life. This comparative study contributes to interfaith understanding, theological dialogue, and academic research in comparative religion.